2021
DOI: 10.1002/aenm.202102845
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Enhanced Kinetics of Sr2Fe1+xMo1‐xO6‐δ Electrocatalysts for High‐Performance Solid Oxide Cells

Abstract: Conventionally, Ni-based cermets are widely used for SOCs as porous fuel materials due to their excellent electrocatalytic activity, thermal and chemical stability, and cost-effectiveness. [13][14][15] However, redox cycles and carbon depositions on Ni will inevitably occur within the fuel electrode, deteriorating their long-term electrochemical performance and stability. [16] Alternatively, perovskite oxides (ABO 3 ) attract significant attention from the scientific community as new potential candidates, [3,[… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 55 publications
1
44
0
Order By: Relevance
“…From the DRT results, four electrochemical processes were identified for SOEC, corresponding to P 1 to P 4 in Figure 5B,D. According to the literature, 45–49 P 1 , P 2 , P 3 , and P 4 correspond to gas diffusion and gas conversion in the fuel electrode supporting layer (0.1–5 Hz), oxygen chemical surface exchange in the oxygen electrode (10 1 –10 2 Hz), charge‐transfer reaction in the fuel electrode (10 2 –10 3 Hz), and the oxygen anion diffusion through the electrolyte or the electrode interface (10 3 –10 4 Hz), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…From the DRT results, four electrochemical processes were identified for SOEC, corresponding to P 1 to P 4 in Figure 5B,D. According to the literature, 45–49 P 1 , P 2 , P 3 , and P 4 correspond to gas diffusion and gas conversion in the fuel electrode supporting layer (0.1–5 Hz), oxygen chemical surface exchange in the oxygen electrode (10 1 –10 2 Hz), charge‐transfer reaction in the fuel electrode (10 2 –10 3 Hz), and the oxygen anion diffusion through the electrolyte or the electrode interface (10 3 –10 4 Hz), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…for the nominal La0.7Ba0.3MnO3 in DFT calculations. This method is widely used in first-principles calculations [41][42][43]. Observable accumulations of charges (electrons) at the interface suggest that the oxygen atoms at the interface are more ionized, hence aiding the creation of Vo.…”
Section: Resultsmentioning
confidence: 99%
“…248,249 Solid oxide fuel/electrolyte cell performance can be altered by optimizing the Fe/Mo ratio. Xi et al 250 found that partially replacing Mo with Fe ions in the Sr 2 Fe 1+ x Mo 1− x O 6− δ system could enhance the metal–oxygen hybridization and shifted their bulk O 2p band energy towards the Fermi level, leading to the reduction of the formation energy of as well as its migration energy. Thus, the formation of defects and oxygen ion transport will be promoted, increasing the adequate contacts between analytes and active B-site transition metals and activating catalytic reaction kinetics.…”
Section: Applications Of Half-metallic Dp Oxidesmentioning
confidence: 99%